Editorial, 2022, 60 years since creation of the Universidad Centroccidental Lisandro Alvarado and 46 years of the Dean of Science and Technology (Publicaciones en Ciencias y Tecnología, 2022)
Within the framework of the sixtieth anniversary of the creation of the Universidad Centroccidental Lisandro Alvarado and the 46 years of the Dean of Science and Technology, this editorial presents the trajectory of both, from its creation to the present, where the events in the country and the world have made universities reinvent themselves in the way of sharing knowledge and in how to stay open to fulfill their mission
Keywords: editorial; UCLA; Dean of Science and Technology